Flow inefficiencies in non-obstructive HCM revealed by kinetic energy and hemodynamic forces on 4D-flow CMR - Pola, K; Ashkir, Z; Myerson, S; Arheden, H; Watkins, H; Neubauer, S; Arvidsson, PM; Raman, B (Oxford University Press, 2024)
Aims: Patients with non-obstructive hypertrophic cardiomyopathy (HCM) exhibit myocardial changes which may cause flow inefficiencies not detectable on echocardiogram. We investigated whether left ventricular (LV) kinetic energy (KE) and hemodynamic forces (HDF) on 4D-flow cardiovascular magnetic resonance (CMR) can provide more sensitive measures of flow in non-obstructive HCM. Methods and results: Ninety participants (70 with non-obstructive HCM and 20 healthy controls) underwent 4D-flow CMR. Patients were categorized as phenotype positive (P+) based on maximum wall thickness (MWT) ≥ 15 mm or ≥13 mm for familial HCM, or pre-hypertrophic sarcomeric variant carriers (P−). LV KE and HDF were computed from 4D-flow CMR. Stroke work was computed using a previously validated non-invasive method. P+ and P− patients and controls had comparable diastolic velocities and LV outflow gradients on echocardiography, LV ejection fraction, and stroke volume on CMR. P+ patients had greater stroke work than P− patients, higher systolic KE compared with controls (5.8 vs. 4.1 mJ, P = 0.0009), and higher late diastolic KE relative to P− patients and controls (2.6 vs. 1.4 vs. 1.9 mJ, P < 0.0001, respectively). MWT was associated with systolic KE (r = 0.5, P < 0.0001) and diastolic KE (r = 0.4, P = 0.005), which also correlated with stroke work. Systolic HDF ratio was increased in P+ patients compared with controls (1.0 vs. 0.8, P = 0.03) and correlated with MWT (r = 0.3, P = 0.004). Diastolic HDF was similar between groups. Sarcomeric variant status was not associated with KE or HDF. Conclusion: Despite normal flow velocities on echocardiography, patients with non-obstructive HCM exhibited greater stroke work, systolic KE and HDF ratio, and late diastolic KE relative to controls. 4D-flow CMR provides more sensitive measures of haemodynamic inefficiencies in HCM, holding promise for clinical trials of novel therapies and clinical surveillance of non-obstructive HCM.